Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5194/acp-14-3247-2014
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ozone loss and ozone mini-hole event during the Arctic winter 2010/2011 as observed by SCIAMACHY and GOME-2

Abstract: Abstract. Record breaking loss of ozone (O 3

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 92 publications
7
42
1
Order By: Relevance
“…MLS loss at these levels is larger than our estimations based on SMILES and SMR ozone. For comparison, the loss derived from SCIAMACHY observations by Hommel et al (2014) in a layer of 475-525 K is of the order of 1 ppmv which is roughly consistent with our results. Note that Hommel et al (2014) used the 38PVU criterion for defining the vortex edge.…”
Section: Comparison With Other Studiessupporting
confidence: 79%
See 2 more Smart Citations
“…MLS loss at these levels is larger than our estimations based on SMILES and SMR ozone. For comparison, the loss derived from SCIAMACHY observations by Hommel et al (2014) in a layer of 475-525 K is of the order of 1 ppmv which is roughly consistent with our results. Note that Hommel et al (2014) used the 38PVU criterion for defining the vortex edge.…”
Section: Comparison With Other Studiessupporting
confidence: 79%
“…Comparable studies of ozone loss in the winter 2009/2010 based on different analysis methods and measurements were done by Kuttippurath et al (2010), Wohltmann et al (2013) and Hommel et al (2014). The inferred loss of SMR ozone agrees with loss simulated using the chemical transport model ATLAS by Wohltmann et al (2013).…”
Section: Comparison With Other Studiesmentioning
confidence: 49%
See 1 more Smart Citation
“…The Arctic winter 2010/2011 has been well analysed, especially with respect to ozone loss (e.g. Manney et al, 2011;Sinnhuber et al, 2011;Arnone et al, 2012;Kuttippurath et al, 2012;Hommel et al, 2014). The dynamical perspective, and thus the exceptional dynamical conditions of this winter, was discussed in detail by Hurwitz et al (2011), Isaksen et al (2012, Strahan et al (2013), and Shaw and Perlwitz (2014).…”
Section: Introductionmentioning
confidence: 99%
“…2009/2010 has been presented by Sagi et al (2014). The comparison concluded that our estimation of the ozone loss is approximately 0.3 ppmv lower than other studies (Kuttippurath et al, 2010;Hommel et al, 2014;Wohltmann et al, 2013) . In Sagi et al (2014) 9 Atmos.…”
Section: Comparison With Other Studiesmentioning
confidence: 54%